Season of birth and schizotypy in a sample of undergraduate students - Szöke, Andrei; Richard, Jean‑Romain; Ladea, Maria; Ferchiou, Aziz; Ouaknine, Elie; Briciu, Victor-Alexandru; Pirlog, Mihail Cristian; Bran, Mihai; Pignon, Baptiste; Schürhoff, Franck (Springer Nature, 2024)
Purpose In line with the psychotic continuum theory, the study of psychometric schizotypy in non-clinical samples has been proposed as a convenient yet powerful method for studying the etiology of psychosis. Based on this paradigm, several studies explored the association between season of birth (SoB) and schizotypy but led to inconsistent results. Building on the analysis of the previous studies, in the present study, we aimed to advance our understanding by improving the methodology (using a homogeneous group, eliminating unreliable respondents, taking into account potential confounders) and the reporting. Methods Subjects were recruited among undergraduate students from 3 Romanian Universities. To limit the potential influence of invalid response, we applied methods for detecting unreliable and/or biased questionnaires and excluded subjects with unreliable/ biased answers from the analyses. Schizotypal dimensions were measured using the Romanian translation of the 22-items Schizotypal Personality Questionnaire-Brief (SPQ-B). The association between schizotypy scores and season of birth was explored using linear regression. Results In a sample of 484 undergraduate students from Romania, we found that being born in late winter/early spring (February and March) was associated to higher total schizotypy score and disorganization. Furthermore, we found that restricting the sample to subjects born in an urban environment increased the strength of the association. Conclusion This study is consistent with an association between SoB and the risk of psychotic disorders.